Patients Can Administer Mobile Audio Recordings to Increase Knowledge in Advanced Prostate Cancer - Daniel H. Kwon; Lauren Trihy; Nika Darvish; Eliza Hearst; Saffanat Sumra; Hala T. Borno; Rohit Bose; Jonathan Chou; Ivan deKouchkovsky; Arpita Desai; Brad Ekstrand; Terence Friedlander; et al. (Cancer Medicine)
ABSTRACT Introduction Consultation audio recordings improve patient decision‐making but are underutilized. Patient‐administered recording apps on mobile devices may increase access, but implementation has not been evaluated. Methods We conducted a single‐arm study delivering education, coaching, and reminders for patients to record their appointment using a mobile recording app. Patients had progressive, advanced prostate cancer and an upcoming appointment where the option of docetaxel would be discussed. We used the RE‐AIM framework for evaluation. Reach was the proportion of patients who participated. Effectiveness was change in informed decision‐making pre‐ vs. post‐appointment. We used a questionnaire evaluating patient knowledge about docetaxel (0%–100% correct) and the decisional conflict scale‐informed subscale (0 = feels extremely uninformed to 100 = extremely informed) to compare means using the paired t‐test. Adoption was the proportion of providers agreeing to be recorded. Implementation was coordinator adherence to intervention delivery. We conducted semistructured interviews with patients, caregivers, and providers to assess barriers, facilitators, and suggestions for recording implementation. Results Of 102 patients approached, 50 (49%) patients participated. Mean age was 75 years, 38 (76%) were Non‐Hispanic White, and 43 (86%) had telehealth appointments. Knowledge increased from 44.7% to 49.5% (p = 0.019), particularly about palliative care (42% answering correctly to 60%, p = 0.035). Decisional conflict‐informed subscale increased from 48.9 to 70.9 (p < 0.001). Forty‐three patients (85%) made a recording, of whom 33 (77%) reported the recording helped treatment decision‐making. All 17 providers agreed to be recorded. Coordinator adherence was high. Multi‐level barriers, suggestions, and facilitators mostly related to intervention complexity and stakeholder compatibility. Conclusion Patient‐administered audio recordings had a positive effect on decision‐making, particularly for palliative care awareness. For broader implementation, efforts should focus on revising institutional policies; teaching patients or caregivers to use existing recording functions on their devices; leveraging artificial intelligence for transcription and summarization; and integrating recording into telehealth technology and electronic patient portals. Trial Registration: https://clinicaltrials.gov/study/NCT05127850